The Association Between Self-Efficacy and Dietary Adherence Among Patients with Chronic Kidney Disease Undergoing Hemodialysis at Medan General Hospital in 2024 - Kamaliah Ainun; Muslimah Pase (Benih : Journal of Midwifery, 2026)
Chronic Kidney Disease (CKD), particularly End-Stage Renal Disease (ESRD), is a progressive and irreversible condition characterized by a gradual decline in renal function, resulting in the inability of the body to maintain metabolic balance and fluid-electrolyte homeostasis. According to data from the Indonesia Renal Registry (IRR), approximately 98% of patients with Chronic Kidney Disease undergo hemodialysis therapy, while only 2% receive peritoneal dialysis (PD). This study aimed to analyze the relationship between self-efficacy and dietary adherence among patients with chronic kidney disease undergoing hemodialysis at Haji General Hospital, Medan, in 2024. This study employed a quantitative approach using a cross-sectional design. The study population consisted of all patients undergoing hemodialysis twice a week. Samples were selected using an accidental sampling technique, resulting in 17 respondents who underwent hemodialysis during the three-day data collection period. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed that among the 17 respondents, most had a moderate level of self-efficacy (10 respondents; 58.8%). Regarding dietary adherence, the majority of patients were non-adherent to the prescribed diet (11 respondents; 64.7%). Statistical analysis revealed a significant association between self-efficacy and dietary adherence among patients with chronic kidney disease undergoing hemodialysis at Haji General Hospital, Medan, with a p-value of 0.007 (p < 0.05). In conclusion, self-efficacy was significantly associated with dietary adherence among patients with chronic kidney disease undergoing hemodialysis at Haji General Hospital, Medan, in 2024. These findings suggest that nutritionists and healthcare professionals should provide continuous nutrition education and counseling to improve patients' dietary adherence.